2015
DOI: 10.1111/vru.12246
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Radiation Therapy and Firocoxib for the Treatment of Canine Nasal Carcinoma

Abstract: Carcinomas represent two-thirds of canine nasosinal neoplasms. Although radiation therapy (RT) is the standard of care, the incidence of local recurrence following treatment is high. Cyclooxygenase-isoform-2 (COX-2) is expressed in 71-95% of canine nasal carcinomas and has been implicated in tumor growth and angiogenesis. Accordingly, COX-2 inhibition seems rational to improve outcome. Dogs with histologically confirmed, previously untreated nasal carcinomas were randomized to receive the combination of a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In many cases curative treatment is not an option and palliative care is opted for. In the studies mentioned above, several factors used to assess quality of life (including appetite, activity levels and pain) were all noted to be improved in patients treated with NSAIDs (reported through owner questionnaires), even in cases where NSAIDs showed no improvement in survival time compared to other treatment options . In one study, most owners requested that their dogs remain on piroxicam treatment even if tumour remission did not occur, due to their subjective improvement in quality of life .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases curative treatment is not an option and palliative care is opted for. In the studies mentioned above, several factors used to assess quality of life (including appetite, activity levels and pain) were all noted to be improved in patients treated with NSAIDs (reported through owner questionnaires), even in cases where NSAIDs showed no improvement in survival time compared to other treatment options . In one study, most owners requested that their dogs remain on piroxicam treatment even if tumour remission did not occur, due to their subjective improvement in quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…In the studies mentioned above, several factors used to assess quality of life (including appetite, activity levels and pain) were all noted to be improved in patients treated with NSAIDs (reported through owner questionnaires), even in cases where NSAIDs showed no improvement in survival time compared to other treatment options. 95,99,101,102 In one study, most owners requested that their dogs remain on piroxicam treatment even if tumour remission did not occur, due to their subjective improvement in quality of life. 95 Given the importance of quality of life, this is clinically relevant finding and should be taken into consideration when decisions are made regarding treatment options in veterinary cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] While radiation therapy can be used to treat a variety of tumor types, nasal tumors are a classic example in which radiation therapy alone is considered standard of care treatment, although optimal protocols remain unclear. [4][5][6][7][8][9][10][11][12][13][14] Prospective, randomized clinical trials are needed to determine the optimal radiation technique and fractionation that provide the most effective means of long-term local control, as is done in human medicine. It is vital that standardized criteria exist in which to assess response to therapy, thereby facilitating determination of the best treatment protocols.…”
mentioning
confidence: 99%
“…A median survival time (MST) of 95 days has been reported for nasal carcinomas if no treatment is pursued . The main goal of therapy is typically to control local disease and treatment is most often radiotherapy (RT) alone, although surgery (rhinotomy), either alone or in combination with RT, is also reported . MSTs following surgery alone are approximately 3–6 months although the procedure is associated with a high rate of morbidity .…”
Section: Introductionmentioning
confidence: 99%
“…A combination of surgical debulking and adjuvant RT has not been proven to increase MSTs . Combining RT with cyclooxygenase‐2 (COX‐2) inhibitors and chemotherapy has also been investigated, but no survival benefit (MST of 201 to 474 days) compared with RT alone was identified . Chemotherapy as a sole treatment is not routinely recommended, but is reported: one study showed some benefit for individual dogs with a clinical response rate of 27% using single‐agent cisplatin treatment .…”
Section: Introductionmentioning
confidence: 99%